P2Y1 Receptor Agonist Attenuates Cardiac Fibroblasts Activation Triggered by TGF-β1 - Tian, Geer; Zhou, Junteng; Quan, Yue; Kong, Qihang; Wu, Wenchao; Liu, Xiaojing (Frontiers in Pharmacology, 2021)
Cardiac fibroblasts (CFs) activation is a hallmark feature of cardiac fibrosis caused by cardiac remodeling. The purinergic signaling molecules have been proven to participate in the activation of CFs. In this study, we explored the expression pattern of P2Y receptor family in the cardiac fibrosis mice model induced by the transverse aortic constriction (TAC) operation and in the activation of CFs triggered by transforming growth factor β1 (TGF-β1) stimulation. We then investigated the role of P2Y1receptor (P2Y1R) in activated CFs. The results showed that among P2Y family members, only P2Y1R was downregulated in the heart tissues of TAC mice. Consistent with our in vivo results, the level of P2Y1R was decreased in the activated CFs, when CFs were treated with TGF-β1. Silencing P2Y1R expression with siP2Y1R accelerated the effects of TGF-β1 on CFs activation. Moreover, the P2Y1R selective antagonist BPTU increased the levels of mRNA and protein of profibrogenic markers, such as connective tissue growth factor (CTGF), periostin (POSTN), and 𝛼-smooth muscle actin(𝛼-SMA). Further, MRS2365, the agonist of P2Y1R, ameliorated the activation of CFs and activated the p38 MAPK and ERK signaling pathways. In conclusion, our findings revealed that upregulating of P2Y1R may attenuate the abnormal activation of CFs via the p38 MAPK and ERK signaling pathway.